Phytochemical insights and neuro-gut axis modulation of Asparagus racemosus (Shatavari) in Postpartum Depression: a mini review with HPTLC-Based justification - D, Dafini; Krishnarajabhatt, Hemavathi Shivapura; Unnikrishnan, Parvathy (Frontiers in Nutrition, 2025)
Approximately 1 in 8 women experience postpartum depression (PPD), which is a serious public health concern. The adverse effects of antidepressant medications and the stigma attached to receiving mental health care impede the adoption of these approaches. Conventional treatments are seen to be low-risk and give women a feeling of control over their improved physical and emotional well-being. Postpartum depression (PPD) is a complex psychiatric condition increasingly understood through the lens of microbiota-gut-brain axis dysregulation. Recent studies underscore the influence of gut microbiota on neuroendocrine balance, serotonin synthesis, and inflammatory pathways, all crucial factors in the onset and progression of PPD. Asparagus racemosus (Shatavari), an Ayurvedic herb traditionally prescribed for women’s reproductive health, is now gaining recognition for its psychobiotic potential. High-Performance Thin-Layer Chromatography (HPTLC) analyses have demonstrated that dry Shatavari contains a significantly richer concentration of bioactive phytoconstituents, such as steroidal saponins and flavonoids, compared to its wet form. These compounds exhibit prebiotic activity, influence microbial composition, and support the modulation of neurotransmitters. This mini review examines the intersection of phytochemical richness in dry A. racemosus and its emerging role in microbiota-mediated mood regulation. It highlights its potential as a botanical psychobiotic and proposes directions for future clinical validation within the context of postpartum mental health frameworks.